Plasmonic Hybrids of MoS2 and 10-nm Nanogap Arrays for Photoluminescence Enhancement - Yang Yang; Ruhao Pan; Shibing Tian; Changzhi Gu; Junjie Li (Micromachines, 2020)
Monolayer MoS2 has attracted tremendous interest, in recent years, due to its novel physical properties and applications in optoelectronic and photonic devices. However, the nature of the atomic-thin thickness of monolayer MoS2 limits its optical absorption and emission, thereby hindering its optoelectronic applications. Hybridizing MoS2 by plasmonic nanostructures is a critical route to enhance its photoluminescence. In this work, the hybrid nanostructure has been proposed by transferring the monolayer MoS2 onto the surface of 10-nm-wide gold nanogap arrays fabricated using the shadow deposition method. By taking advantage of the localized surface plasmon resonance arising in the nanogaps, a photoluminescence enhancement of ~20-fold was achieved through adjusting the length of nanogaps. Our results demonstrate the feasibility of a giant photoluminescence enhancement for this hybrid of MoS2/10-nm nanogap arrays, promising its further applications in photodetectors, sensors, and emitters.